2015
DOI: 10.1042/bsr20150084
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-148b suppresses hepatic cancer stem cell by targeting neuropilin-1

Abstract: SynopsisThe existence of cancer stem cells (CSCs) is considered as a direct reason for the failure of clinic treatment in hepatocellular carcinoma (HCC). Growing evidences have demonstrated that miRNAs play an important role in regulation of stem cell proliferation, differentiation and self-renewal and their aberrances cause the formation of CSCs and eventually result in carcinogenesis. We recently identified miRNA-148b as one of the miRNAs specifically down-regulated in side population (SP) cells of PLC/PRF/5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 36 publications
5
53
1
Order By: Relevance
“…Cell invasion assay was assessed using the Millipore 24‐well Millicell Chamber of pore size 8 μm (Millipore), according to Liu et al (). Briefly, the cells (2 × 10 5 ) in DMEM without FBS were added into the upper chamber pre‐coated with Matrigel (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…Cell invasion assay was assessed using the Millipore 24‐well Millicell Chamber of pore size 8 μm (Millipore), according to Liu et al (). Briefly, the cells (2 × 10 5 ) in DMEM without FBS were added into the upper chamber pre‐coated with Matrigel (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…miR-491 blocks the activation of NF-kB by regulating GIT-1 and inhibiting extracellular signal-regulated kinase (ERK), thereby reducing the stemness of HCSCs [26]. miR-148b restrains the formation of side population (SP) cells by regulating NRP1 and also helps regulate the proliferation, drug resistance, metastasis and angiogenesis of HCSCs [27]. In recent years, studies have shown that EMT plays an important role in tumor invasion and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of HCC stem cells has been regarded as the immediate cause of clinical tumor recurrence and treatment failure for patients with HCC . Conventional ways of surgery, chemotherapy, and radiotherapy can kill a majority of carcinoma cells, but it is hard to eradicate cancer stem cells that maintain a high capacity for self‐renewal, chemoresistance, and pluripotency, leading to frequent recurrence or metastasis in patients with HCC . Therefore, there is an urgent need for new therapy strategies that could directly target HCC stem cells.…”
Section: Introductionmentioning
confidence: 99%